Study of a gang risk intervention program: a profile of at-risk youth in the public school setting - Muller, Patrick Saint Francis (2001)
The purpose of this study was (1) to review programs directed towards students defined at risk in the literature, (2) to construct a profile of the at-risk population served by the Gang Risk Intervention Program (GRIP) in Riverside County, and (3) to make future recommendations towards enhanced service delivery to the same